Colorimetric Screen-Printed Label Using Low Molecular Weight Chitosan Grafted with Rosolic Acid for pH and Ammonia Gas Sensing - Ronte, Arnat; Chalitangkoon, Jongjit; Monvisade, Pathavuth (My University, 2024)
Colorimetric sensing technologies are valued for their simplicity and adaptability, yet their large-scale production remains economically challenging. This study presents a cost-effective colorimetric pH sensor developed from low molecular weight chitosan (LC) grafted with rosolic acid (LCRA), engineered as a pH-sensitive colorant for screen-printing inks. LCRA was synthesized via a Mannich reaction and characterized using1 H NMR, FT-IR, and UV-Vis spectroscopy. LCRA showed reduced crystallinity and thermal stability alongside notable improvements in water solubility compared to its LC precursor. The LCRA ink displayed compatibility with various substrates, including polypropylene spun bond, filter paper, and cotton, applying easily via screen printing without any dye leaching. Notably, it exhibited a responsive color change from orange-yellow to pink-red in response to pH adjustments between 4.0 and 12.0 and upon exposure to ammonia gas. These findings position the LCRA label as a versatile and efficient solution for visual pH detection across various applications.
Keywords: ammonia sensor; chitosan; pH sensor; polymeric dye; rosolic acid; screen-printing